Formulation Formulation of NU and Muhammadiyah Da'wah Among Millennial Generations During the Covid 19 Pandemic - Rahmi, Amelia; Dadang Abdullah, Asep; Purwati, Eka; Imron, Ali (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
The study aims to answer how the formulation of da'wah of the two major religious organizations in Indonesia for the existing millennial generation during the Covid 19 pandemic. Primary data was collected through three choices of interview models, namely direct, virtual, or through filling out instruments, adjusting to the implementation of PPKM. It was found that NU's da'wah for the millennial generation during the Covid 19 pandemic was carried out with two da'wah models, online and offline by implementing health protocols. Muhammadiyah did the same thing even though the intensity of offline da'wah had decreased drastically. During the pandemic, Muhammadiyah emphasized da'wah with action to overcome the social impact of the Covid 19 pandemic. PBNU and PP. Muhammadiyah has not set a standard da'wah formulation for the millennial generation during the pandemic. Nevertheless, PBNU has disseminated the discourse on the formulation to regional and branch administrators in the form of general policies. At Muhammadiyah, efforts to formulate formulations were carried out through the collaboration of the IT team, the Library and Information Council, and the Muhammadiyah Covid-19 Command Center (MCCC). In the future, NU and Muhammadiyah need to conduct transdisciplinary studies and formulate the intended formulation to facilitate da'wah operations for millennials, especially during the pandemic.